Encapsulation of Cyclotetramethylenetetranitramine (HMX) by Electrostatically Self‐Assembled Graphene Oxide for Desensitization. Issue 9 (7th July 2017) - Liu, Tao; Geng, Chengzhen; Zheng, Baohui; Li, Shangbin; Luo, Guan
Abstract: To improve the safety of cyclotetramethylenetetranitramine (HMX) particles, a novel strategy was developed for the fabrication of graphene oxide encapsulated HMX (HMX@GO) by electrostatic self‐assembly between graphene oxide and HMX particles. The prepared samples were characterized by optical microscopy, scanning electron microscopy, Raman spectroscopy, X‐ray photon spectroscopy, thermogravimetry, differential scanning calorimetry and water contact angle tests. The results revealed that GO sheets were coated densely and homogeneously on the HMX particles in a HMX@GO composite at a low GO content of about 0.23 wt %. Compared with that of raw HMX, the impact sensitivity of the HMX@GO composite decreased from 100 % to 30 %, and the 50 % probability of required ignition energy (E50 ) in the electrostatic spark sensitivity test increased from 0.66 J for HMX to 1.12 J for the HMX@GO composite, suggesting that the electrostatically self‐assembled GO coating layer could obviously enhance the safety of HMX. Abstract :